2019
DOI: 10.24136/oc.2019.030
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of energy balances with dominant coal consumption in European economies and Turkey in the years 1990?2017

Abstract: Research background: Energy policy is closely linked to economic development. Therefore, its optimization is an important issue especially in the contemporary European environmental conditions.  EU regulations enforce a reduction of carbon dioxide emissions and the abandonment of non-renewable energy resources. Instead, they promote renewable energy sources. In this way, new legal and environmental circumstances are becoming the main reason for the transformation of energy balances, which is a real economic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Undoubtedly, the globalization processes have led to systematic socio-economic development in most world economies, combined with a significant increase in the level of innovation, the level of investment outlays and the level of foreign direct investment [9][10][11][12][13][14][15][16]. Globalization processes have also contributed to the emergence of new lifestyles and consumption styles [17][18][19][20], which together with the increase in the wealth of the society and the level of innovation in enterprises contributed to the creation of the renewable energy (RE) sector, which is one of the fastest developing branches of the world economy [21][22][23][24][25]. Currently, there is a systematic increase in the RE sector in terms of production and research, which results in the increase of efficiency in sourcing RE and the decrease in the prices of RE sector installations, which simultaneously contributes to its further development.…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, the globalization processes have led to systematic socio-economic development in most world economies, combined with a significant increase in the level of innovation, the level of investment outlays and the level of foreign direct investment [9][10][11][12][13][14][15][16]. Globalization processes have also contributed to the emergence of new lifestyles and consumption styles [17][18][19][20], which together with the increase in the wealth of the society and the level of innovation in enterprises contributed to the creation of the renewable energy (RE) sector, which is one of the fastest developing branches of the world economy [21][22][23][24][25]. Currently, there is a systematic increase in the RE sector in terms of production and research, which results in the increase of efficiency in sourcing RE and the decrease in the prices of RE sector installations, which simultaneously contributes to its further development.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with the sectorial analysis, the current research confirms that such traditional "non-ecological" sectors as petroleum companies are strongly affected by green-factor policies [5] affecting their capitalization, which creates not only soft social pressure, but is also a source of direct financial incentives [6,7]. The results provided by Filimonova et al (2020) demonstrate that many investors support the idea that the petroleum companies with solid environmental performances are more promising, from the investment standpoint, than businesses with roughly the same financial performance but lower environmental indicators [8].…”
Section: Literature Reviewmentioning
confidence: 56%
“…His research confirmed the long-term, difficult-to-change, structural diversity between the EU economies [11][12][13]. Thus, in their study, Jonek-Kowalska (2019) found an increasing share of renewable sources in the energy balance, but this growth is very slow in the EU and in Turkey in 1990-2017 [7]. The countries in question tend to choose the strategy, following which they decrease the share of coal, but at the same time increase their share of gas.…”
Section: Literature Reviewmentioning
confidence: 76%
See 1 more Smart Citation
“…Circular economy primarily means ensuring the functioning of materials and resources in the economy for as long as possible. This concept implies cooperation, which means that business models and enterprise functioning frameworks should change, whereas consumers and the legal and institutional environment should be prepared for such changes (Krysovatyy et al, 2018;Razminiene, 2019;Jonek-Kowalska, 2019). The assumption of circular economy is also to implement full waste recovery at the local level (Council of Ministers, 2019, p. 14).…”
Section: Introductionmentioning
confidence: 99%